Airway function in infants with vascular rings: preoperative and postoperative assessment. Issue 2 (February 1990) - Thomson, A H; Beardsmore, C S; Firmin, R; Leanage, R; Simpson, H
Abstract : Aortic arch anomalies in infancy often cause intrathoracic airway obstruction. Airway function was assessed as part of the diagnostic evaluation in six symptomatic infants both by plethysmography and using a chest compression technique to obtain partial flow-volume loops. Two infants had normal intrathoracic airway function and their symptoms were unrelated to aortic arch abnormalities. The remaining four had complete vascular rings (three double aortic arch, one pulmonary sling) and had increased expiratory airway resistance (Raw) (mean Raw = 700% predicted) and greatly decreased maximum flow rates at functional residual capacity (VmaxFRC; mean VmaxFRC = 34% predicted) with gross shape abnormalities of the flow-volume loop. Postoperatively airway function was substantially improved (mean Raw = 175% predicted, VmaxFRC = 79% predicted) but some abnormality of flow-volume loop shape remained, suggesting that tracheal dynamics were not completely normal in the early postoperative period.